High Aspirations and Limited Opportunities: A Comparison of Education Quality in the MENA Region and its Implications for Youth. - Farah, Samar (Muslim World, 2017)
The article discusses the education system in the Middle East and North Africa (MENA) region which uses two international assessments, and mentions trends in mathematics and science study and program for international student assessment. Topics discussed include unemployment rate in Gaza, challenges in education policy, and topography of education across MENA region.